Penguatan Kelembagaan Bank Sampah Berbasis Filantropi: Studi pada Sedekah Sampah Berkah (SSB) - Amerti Widowati; Surjawati Surjawati; Wahdi NS (Indo Publishing, 2026)
This Community Service Program (PkM) was conducted at Sedekah Sampah Berkah (SSB), a philanthropy-based community waste bank established in 2020. The objective of this program was to identify the strengths and challenges faced by SSB in managing its activities and to formulate recommendations for institutional strengthening to improve effectiveness and sustainability. The implementation methods included needs assessment, presentation of waste bank management strategies, participatory discussions, and joint evaluation with partners. The results indicate that SSB’s main strengths lie in active volunteer and donor participation, as well as the economic potential of recyclable waste with high market value. During the period of 2020–2022, SSB was able to generate approximately IDR 5,000,000 every two weeks from waste donations. However, several challenges were identified, including the need to strengthen administrative systems, financial transparency, and long-term organizational sustainability strategies. The level of program success is reflected in the increased understanding of systematic governance among the management team and their commitment to improving operational practices. This program contributes to strengthening institutional capacity and supports the development of a sustainable, community-based and philanthropy-driven waste management model.